The assessment of the degree of softening during the hardened steel wheels tempering - Vakulenko, L. I.; Nadezhdin, Yu. L. (Science and Transport Progress, 2010)
The issues re. estimation of changes in hardness and sound vibration propagation velocity after tempering the hardened railway wheel steel are considered.